Applicability of ISNT Rule Using BMO-MRW to Differentiate Between Healthy and Glaucomatous Eyes. Issue 7 (July 2018) - Park, Do Young; Lee, Eun Jung; Han, Jong Chul; Kee, Changwon
Abstract : Purpose: We evaluated the applicability of the ISNT rule using Bruch's membrane opening minimum rim width (BMO-MRW) in healthy eyes and eyes with normal tension glaucoma (NTG). Materials and Methods: In total, 124 healthy eyes and 136 NTG eyes were analyzed. Using 2-dimensional disc photographs, neuroretinal rim (NRR) thickness was measured at the superior, inferior, nasal, and temporal sides of the optic disc. Using spectral domain-optical coherence tomography, BMO-MRW was measured at the same regions. We compared the applicability of the ISNT rule in healthy and NTG eyes between these 2 methods. If the NRR was not clearly distinguished on disc photographs, the eye was classified into the "indistinguishable NRR" group and we only tested applicability of the ISNT rule using BMO-MRW. Results: The specificity of "violation of the ISNT rule" for the diagnosis of glaucoma was higher when BMO-MRW was used (66.3%) than using disc photographs (42.2%), whereas the sensitivity did not show a significant difference between the 2 methods (91.7% vs. 86.5%). Compared with eyes with distinguishable NRR (179 eyes), eyes with indistinguishable NRR (81 eyes) had higher axial length, more negative refractive error, and higher tilt ratio ( P <0.001). The diagnostic ability of "violation of ISNT rule" using BMO-MRW was not significantly different between eyes with indistinguishable NRR and those with distinguishable NRR ( P >0.05). Conclusions: Application of the ISNT rule using BMO-MRW shows superiority in distinguishing between healthy and glaucomatous optic discs compared with disc photographs. The ISNT rule can be applied using BMO-MRW even when NRR is indistinguishable on disc photographs, such as in myopic tilted discs.